Lessons learned about ageing and gerontological nursing in South Africa - Staja Q. Booker (AOSIS, 2015)
Background: The unprecedented global growth in older adults merits high-quality gerontological nursing care. As gerontological nursing grows in visibility in developed and developing countries, nurses must possess a broader worldview of ageing with knowledge of physiological, psychosocial, and cultural issues. Purpose: The purpose of this article is to: (1) highlight lessons learned on differences and similarities in ageing and care of older adults in the United States of America (USA) and South Africa (SA); and (2) provide recommendations on how to advance gerontological nursingeducation in SA. Methods: A two-week international service-learning project was undertaken by visiting SA and learning about their nursing system and care of older adults. Service-learning is an innovative teaching-learning-service method that provided reflective and hands-on experience of gerontological nursing. This article provides a personal reflection of lessons learned about ageing and gerontological nursing during the service-learning project. Findings: Care of older adults in SA is in many ways different from and similar to that in the USA. Consequently global nurses should recognise those differences and provide culturally appropriate care. This service-learning experience also demonstrated the need for gerontological nursing education in SA. Based on this, recommendations on how to infuse and advance gerontological nursing education in SA are provided. Conclusion: Caring for older adults in a global context requires knowledge and understanding of cultures and their values and practices. With a growing population of diverse older adults, there is a need for incorporation